Sorghum Association Panel whole‐genome sequencing establishes cornerstone resource for dissecting genomic diversity. (5th July 2022) - Boatwright, J. Lucas; Sapkota, Sirjan; Jin, Hongyu; Schnable, James C.; Brenton, Zachary; Boyles, Richard; Kresovich, Stephen
SUMMARY: Association mapping panels represent foundational resources for understanding the genetic basis of phenotypic diversity and serve to advance plant breeding by exploring genetic variation across diverse accessions. We report the whole‐genome sequencing (WGS) of 400 sorghum ( Sorghum bicolor (L.) Moench) accessions from the Sorghum Association Panel (SAP) at an average coverage of 38× (25–72×), enabling the development of a high‐density genomic marker set of 43 983 694 variants including single‐nucleotide polymorphisms (approximately 38 million), insertions/deletions (indels) (approximately 5 million), and copy number variants (CNVs) (approximately 170 000). We observe slightly more deletions among indels and a much higher prevalence of deletions among CNVs compared to insertions. This new marker set enabled the identification of several novel putative genomic associations for plant height and tannin content, which were not identified when using previous lower‐density marker sets. WGS identified and scored variants in 5‐kb bins where available genotyping‐by‐sequencing (GBS) data captured no variants, with half of all bins in the genome falling into this category. The predictive ability of genomic best unbiased linear predictor (GBLUP) models was increased by an average of 30% by using WGS markers rather than GBS markers. We identified 18 selection peaks across subpopulations that formed due to evolutionary divergence during domestication, and we found six Fst peaks resulting from comparisons between converted lines and breeding lines within the SAP that were distinct from the peaks associated with historic selection. This population has served and continues to serve as a significant public resource for sorghum research and demonstrates the value of improving upon existing genomic resources. Significance Statement: The whole‐genome sequencing of the sorghum association panel, which represents the most heavily utilized panel in sorghum breeding, will serve as a pivotal resource in the sorghum community to provide improved genotype‐to‐phenotype associations, genomic prediction, and pan‐genome graph construction as demonstrated here. These data will support ongoing and future research focused on gene discovery and trait introgression in the sorghum community and further provide insights into the historic selection and domestication of this multi‐purpose crop.